Pengaruh Work-Life Balance Terhadap Produktivitas Kerja Di Kalangan Generasi Z Pada Outlet Pizza Hut Di Kota Samarinda - Lestari, Nurfadila (Jurnal Mirai Management, 2025)
This study aims to examine the effect of work-life balance (WLB) on the productivity of Generation Z (Gen Z) employees at Pizza Hut outlets in Samarinda, Indonesia. The research method used was quantitative. The research used was population research with a total of 55 Gen Z employees at three outlets. Data analysis was performed using simple linear regression. The results showed that WLB had a positive and significant influence on employee productivity, WLB accounted for 50.6% of the increase in productivity. This finding confirms that a balanced implementation of WLB can significantly increase the productivity and retention of Gen Z employees.